DID DESCARTES COMMIT AN ERROR? NEW DIMENSIONS FOR COGITO ARCHITECTURE. - Yevarouski, Valery (Problems / Problemos, 2017)
The approaches to brain-mind-environment interaction practiced within classical epistemology, modern neurophilosophy, and neuroscience are considered together with the comparative research design,. The concept of natural dualism is introduced. On above grounds, the operational or protopraxis model of behaviour is discussed, which is based on the rigid distinctions between useful, harmful, and neutral fragments selected during life. For the human being, the environment is not limited to nature but includes the body as well as many cognitive processes. The question is who (or what) benefits in the end, if even our internal world is adjusted to its demands. By now it is a construct with philosophically presupposed meaning, which also can be interpreted as both cogito and the Self. Philosophy of psychiatry may propose the minimal or non-programmed cogito as an alternative starting point. This system can be enriched with two more elements - affective cogito and reward centre. Thus, we receive a harmonious categorical structure for the description of psyche and its external activity or practice.